The Role of Value Creativity Capabilities as a Driving Force to Address Customer Boycott Behaviour Through the Mediating Role of Marketing Excellence - Muthanna Twfiq Abdul –Hassan; Mohammed Ahmed Mhmood; Roaa Abdul Kareem Sahib (International Forum of Researchers and Lecturers, 2025)
The current research seeks to identify the role of value Creativity capabilities through its dimensions (environmental value, utility value, achievement value, intrinsic value) in addressing the behaviour of the customer boycott, through the mediating role of marketing excellence through its dimensions (service quality, customer retention, innovation of new services, appropriate price, continuous improvement) in Zain Iraq and Asia Cell in the Middle Euphrates region in (Najaf, Karbala, Babylon, Diwaniyah, Muthanna). The problem of the study lies in the main question of what is the nature of the relationship between the capabilities of value Creativity and the behaviour of the customer boycott with the presence of the mediating role of marketing excellence, and the study used the questionnaire to collect data, as it distributed (112) questionnaire forms to a random sample of administrative leaders in (Zain Iraq and Asia Cell), and retrieved (104) forms valid for statistical analysis and the data collected was analysed using a set of statistical tests available in the two statistical programmes (SPSS. V.29, 29 (Amos.V. 29), The results of the study confirmed a number of conclusions, the most important of which is the existence of a role for value Creativity capabilities in addressing the behaviour of the customer boycott through the mediating role of marketing excellence, which means the company's interest in improving the level of customer satisfaction by investing its capabilities by providing services and products that meet their needs.